Detection of blood Gb3 deposits as a new tool for diagnosis and therapy monitoring in patients with classic Fabry disease. (4th July 2018) - Üçeyler, N.; Böttger, J.; Henkel, L.; Langjahr, M.; Mayer, C.; Nordbeck, P.; Wanner, C.; Sommer, C.
Abstract: Background: The X‐linked Fabry disease (FD) is a multiorgan disorder due to alpha‐galactosidase A (α‐GAL) deficiency with consequent lysosomal accumulation of globotriaosylceramide (Gb3). We established the immunocytochemical detection of Gb3 in blood cells of FD patients as a new method for FD diagnostics, follow‐up and treatment control. Methods: We enrolled 67 FD patients (37 men, 30 women) and 52 healthy controls (26 men, 26 women). PBMC were isolated from whole venous blood and 3x10 5 cells were immunoreacted with antibodies against CD77 as a marker for Gb3. Using fluorescence microscopy, the mean percentage of Gb3 positive PBMC was determined by an investigator blinded to subject allocation. As a second method, we qualitatively assessed Gb3 positive cells in blood smears. Results: Gb3 deposits were unequivocally visible in PBMC and in blood smears. Men ( P < 0.001) and women ( P < 0.01) with classical FD had more Gb3‐positive PBMC than healthy controls, whose samples only occasionally showed positive cells. The number of Gb3 positive PBMC was negatively correlated with α‐GAL activity and positively correlated with plasma lyso‐Gb3 levels. Only the PBMC Gb3 load but not plasma lyso‐Gb3 reflected short‐ and long‐term effects of enzyme replacement therapy ( P < 0.01). Conclusions: Gb3 can be visualized in PBMC and blood smears and can be used as a novel marker for diagnostics, follow‐up and treatment control in FD.